EUPHEMISMS IN THE NEWS OF THE DAGO ELOS CONFLICT - Galih, Alifa; Arimi, Sailal (Prologue: Journal on Language and Literature, 2024)
The internet has become a leading platform for news and media content, providing a diverse range of reading and viewing options for the public. News remains reliable because it offers current and factual information. A noteworthy story in recent news has been the eviction at Dago Elos. This study applies Van Dijk’s Critical Discourse Analysis (CDA) to examine the use of euphemism in media reports on the Dago Elos eviction, aiming to identify the forms of euphemism and understand their function within the context of news discourse. Data for this study consist of linguistic units containing euphemisms—expressions that soften or mask potentially offensive or sensitive content—sourced from four online media outlets reporting on the Dago Elos eviction. This study used a descriptive qualitative approach for analysis, with data collection through a documentation technique. Results from the analysis revealed 16 instances of euphemism across four online news reports on the Dago Elos conflict. The findings suggest that these euphemisms serve to moderate the perceived severity of events, reflecting broader dynamics of power and ideology in news discourse.